Analisis Pelaksanaan Proses Penerimaan dan Penyimpanan Buah dan Sayuran di Kitchen Hotel Mercure Surabaya Grand Mirama (Jurnal Manajemen Pariwisata dan Perhotelan, 2025)
Fruits and vegetables are perishable food items that require special handling during both the receiving and storage processes. The purpose of this study is to investigate the implementation of fruit and vegetable receiving and storage processes in the kitchen of Hotel Mercure Surabaya Grand Mirama. This research employs two approaches: quantitative descriptive and qualitative. Data collection techniques include questionnaires, interviews, and documentation studies. The data analysis technique used is descriptive quantitative analysis, where questionnaire results are calculated using a percentage formula (%) and described using percentage interpretation criteria. Based on the findings, the implementation of fruit and vegetable receiving processes at Hotel Mercure Surabaya Grand Mirama shows that indicators for product freshness, material inspection, rejection of non-conforming materials, sorting, and washing are categorized as good. However, the indicator for material cleanliness falls under the fair category. Meanwhile, the implementation of storage processes, including storage temperature, storage facilities, storage inspection, and the application of the FIFO (First In First Out) storage method, demonstrates a very good criterion. Nevertheless, material separation received a good criterion, indicating room for further improvement to optimize storage management and ensure compliance with established standards.